Analysis of Uncollectible Receivables on the Turnover Rate of Receivables at Hotel X - WULANDARI , Kadek agustin; SEPTIVIARI, Anak Agung Istri M.; YUSMARISA, Ni Luh Riska (Journal of Governance, Taxation and Auditing, 2025)
This study aims to find out the extent of the influence of uncollectible receivables on the turnover rate of receivables at Hotel X. Uncollectible receivables arise when customers do not complete payment obligations within the 30-day maturity period. This condition has the potential to reduce liquidity and operational efficiency of the company. This study uses a quantitative descriptive method with secondary data in the form of receivables statements and hotel financial statements for the 2021–2024 period. The analysis is carried out through the calculation of the receivables turnover ratio to assess the effectiveness of receivables management. The results of the study show a significant increase in uncollectible receivables in 2024. The increase has an impact on the decrease in the receivables turnover rate, which reflects the weakening of the effectiveness of receivables management. Thus, it is necessary to control non-collectible receivables more optimally to maintain smooth cash flow and financial performance of hotels.